2020
DOI: 10.1101/2020.01.06.895938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative molecular profiling of autoreactive CD4 T cells in autoimmune hepatitis

Abstract: Background & Aims: In most autoimmune disorders, crosstalk of B cells and CD4 T cells resultsin the accumulation of autoantibodies. In autoimmune hepatitis (AIH), the presence of anti-Soluble Liver Antigen (SLA or SepSecs) autoantibodies is associated with significantly reduced overall survival, but the associated autoreactive CD4 T cells have not been characterized yet.Here we isolated and deeply characterized SLA-specific CD4 T cells in AIH patients. Methods: We used brief ex vivo restimulation with overlapp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Three groups have recently published observations relevant to the pathogenesis of AIH. Renand et al describe a rare population of CD4 cells, with a memory PD-1 + CXCR5 − CCR6 − CD27 + phenotype, reactive with SLA and only present in patients positive for anti-SLA autoantibodies [ 84 ]. They also describe another phenotype, CD45RA- PD1 + CD38 + -CXCR5-CD127-CD27 + , that when present on CD8 T cells is associated with transaminase levels, while when present on CD4 cells is linked to IgG levels [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three groups have recently published observations relevant to the pathogenesis of AIH. Renand et al describe a rare population of CD4 cells, with a memory PD-1 + CXCR5 − CCR6 − CD27 + phenotype, reactive with SLA and only present in patients positive for anti-SLA autoantibodies [ 84 ]. They also describe another phenotype, CD45RA- PD1 + CD38 + -CXCR5-CD127-CD27 + , that when present on CD8 T cells is associated with transaminase levels, while when present on CD4 cells is linked to IgG levels [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…Renand et al describe a rare population of CD4 cells, with a memory PD-1 + CXCR5 − CCR6 − CD27 + phenotype, reactive with SLA and only present in patients positive for anti-SLA autoantibodies [ 84 ]. They also describe another phenotype, CD45RA- PD1 + CD38 + -CXCR5-CD127-CD27 + , that when present on CD8 T cells is associated with transaminase levels, while when present on CD4 cells is linked to IgG levels [ 84 ]. You et al reported that tissue resident CD8 T (CD8TRM) cells are elevated in the liver of patients with AIH compared to CHB, non-alcoholic fatty liver disease and healthy control tissues [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…These cells are similar in profile to so called T peripheral helper (Tph) cells that have been identified as drivers of B cell inflammation in other autoimmune conditions such as Rheumatoid Arthritis and IgG4related disease (24). The population of PD1 positive activated Tph cells was expanded amongst all CD4 T cells in AIH, produced IL-21 and interferon gamma (IFNg) on ex-vivo restimulation and drove B cell differentiation in co-cultures (23).…”
Section: Activation Of B Cells and Igg Productionmentioning
confidence: 87%
“…T cell expression of activation markers PD1 and CD38 and the magnitude of ex-vivo cytokine responses towards autoantigenic peptides correlates with AIH disease activity (20)(21)(22). Autoreactive T cell responses specific to autoantigen SLA have been investigated by flow cytometry and single cell RNA sequencing (23), showing SLA CD4 T cells transcriptionally upregulate expression of genes associated with B cell help and inflammation. These cells are similar in profile to so called T peripheral helper (Tph) cells that have been identified as drivers of B cell inflammation in other autoimmune conditions such as Rheumatoid Arthritis and IgG4related disease (24).…”
Section: Activation Of B Cells and Igg Productionmentioning
confidence: 99%
“…In this work, T cells from autoimmune hepatitis patients were stimulated in vitro with peptides derived from soluble liver antigen, an autoantibody target in autoimmune hepatitis, and the phenotype and repertoire of responsive T cells were characterized. 51 Remarkably, the T cells that responded to soluble liver antigen peptides were highly enriched in a Tph cell phenotype, with expression of PD-1 but not CXCR5, and single-cell RNA-seq analyses revealed a typical Tph signature, with expression of IL21, ICOS, MAF, TIGIT, and SLAMF6. Peripheral blood cell analyses confirmed an increased frequency of PD-1 + CXCR5 -Tph cells in the circulation of patients with autoimmune hepatitis; these cells could stimulate B cell responses in vitro, consistent with a B cell-helper function.…”
Section: S E Arche S For Anti G En -S Pecifi C Cell S Hi G Hli G Ht T...mentioning
confidence: 94%